2011
DOI: 10.1007/s11605-010-1371-z
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Intraoperative Anastomotic Testing May Avoid Early Gastrointestinal Anastomotic Complications. A Prospective Study

Abstract: Endoscopic anastomotic testing was a safe and reliable method to assess integrity of gastrointestinal anastomoses, to correct any defect under direct visualization, and to avoid early complications. However, this method seemed inadequate to predict late anastomotic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 22 publications
2
21
0
3
Order By: Relevance
“…Lieto et al . and Shamiyeh et al . introduced intra‐operative FE on a routine basis which raises concerns for selection bias when comparing the reported leak rate to other studies.…”
Section: Resultsmentioning
confidence: 92%
“…Lieto et al . and Shamiyeh et al . introduced intra‐operative FE on a routine basis which raises concerns for selection bias when comparing the reported leak rate to other studies.…”
Section: Resultsmentioning
confidence: 92%
“…The thirteen reviewed studies included a total of N=3,023 patients (Table 3), [16,17,[19][20][21][22][23][24][25][26][27][28][29]. Study sample size and design was variable.…”
Section: Resultsmentioning
confidence: 99%
“…Suture repair (74.7%) was the most common method of anastomosis correction used followed by takedown and re-anastomosis (17.3%) and diversion (8.0%). No significant differences in intraoperative leak rates were found were found across anastomosis types (staple: 4.9%, suture: 2.3%, and compression: 0.0%, p=0.066) in the 10 studies that reported leak based on type of anastomosis employed [16,[19][20][21][22][24][25][26][27][28]. Six articles reported on the rate of intraoperative leaks by surgical technique used (laparoscopic v. open) [22,[25][26][27][28][29].…”
Section: Search Term Description Definitionmentioning
confidence: 93%
See 2 more Smart Citations